Motives and Effectiveness of Forex Interventions : Evidence from Peru - Tashu, Melesse (IMF Working Papers; Working Paper, 2014)
This paper assesses empirically the motives and effectiveness of forex interventions in Peru. While the central bank of Peru states that its forex interventions aim only at containing excessive exchange rate volatility, the results of this paper show that, in practice, the interventions seem to have aimed at 'leaning against the wind' as well. The results also show that forex sales, but not forex purchases, react to volatility, indicating asymmetry in the central bank's reactions to episodes of appreciation and depreciation pressures. Similarly, the paper documents evidence of asymmetry in the effectiveness of forex interventions.